A study On the Prevalence of the causes of low vision in patients referring to and examined in low-vision clinic of Rehabilitation Sciences, Shahid Beheshti Medical University - Mohsen Akhgary (Ṭibb-i Tavānbakhshī, 2012)
Background and Aim: The goal of this study is to investigate the severity of visual acuity loss and the causes of low vision as well as the association between the severity of visual acuity loss and the type of low vision aid prescribedMaterial & Methods: In this retrospective cross- sectional study, 204 files of the patients referred to the Low Vision Center of the College of Rehabilitation, between 2007 to 2008, were analyzed. Data about their visual acuity, causes of low vision, and visual aid prescribed for them were collected. SPSS 17 was used to analyze the data.Results: The prevalence of different levels of visual acuity loss was as follow: moderate (40.7%), severe (45.6%), and very severe (13.7%). Twenty five types of diseases were identified with the following prevalence: Diabetic Retinopathy 16.2%, Age related macular degeneration 14.2%, Stargart 12.3%, Retinitis Pigmentosa 10.8%, and Albinism 8.2%. Conclusion: Considering the high prevalence of diabetic retinopathy and ARMD, preventive measures should be taken to reduce these causes of Low vision. Microscope is the most prescribed vision aid for three groups of vision loss. The preference of the Iranian patients for using this vision aid could be due to its more casual appearance and ease of use.